Teachers’ performance at Islamic School Foundations: The impact of self-efficacy, organizational culture, environment, and job satisfaction - Virgana Virgana; Soeparlan Kasyadi (International Journal of Educational Management and Development Studies)
Enhancing organizational performance is key to producing high-quality graduates. Therefore, supporting factors such as self-efficacy, work culture, work environment, and job satisfaction is essential in an educational setting. This study analyzes the direct and indirect influence of these factors on teachers' performance using path analysis with Smart Partial Least Squares software. The sample consisted of 340 teachers from private schools managed by an Islamic religious education foundation. The results showed that self-efficacy, organizational culture, and work environment positively influenced job satisfaction. Additionally, self-efficacy, organizational culture, work environment, and job satisfaction positively impacted teachers' performance. Furthermore, self-efficacy, organizational culture, and work environment had a significant indirect effect on teachers' performance through job satisfaction. These findings suggest that further efforts should focus on enhancing the work environment to provide the best possible service to students, thereby potentially improving their academic achievements. Findings call for follow-up actions by local and central governments, particularly in improving the quality and quantity of equipment at the school level. Ensuring a supportive work environment is crucial for enhancing teachers' psychological satisfaction and encouraging better performance in providing professional services to students. Ensuring that job satisfaction remains high or improves is crucial, as it has a direct impact on the effectiveness of teaching and learning.